Platelet aggregation induced by Caco-2 cells: regulation by matrix metalloproteinase-2 and adenosine diphosphate - RADOMSKI, MAREK; SANTOS-MARTINEZ, MARIA; MEDINA MARTIN, CARLOS (My University, 2006)
Formation of tumor cell-platelet aggregates facilitates hematogenous metastases. However, molecular mechanisms implicated in tumor cell-induced platelet aggregation (TCIPA) in colon cancer are unclear. To investigate mechanisms of TCIPA induced by colon adenocarcinoma cells in vitro, human Caco-2 cells were used to study their interactions with platelets using aggregometry, zymography, phase-contrast microscopy, and flow cytometry. Caco-2-induced platelet aggregation in a concentration-dependent manner. This aggregation resulted in the release of matrix metalloproteinase (MMP)-2, as measured by zymography. In addition, flow cytometry showed a significant up-regulation of activated GpIIb/IIIa, total GpIIb/IIIa, GpIb, and P-selectin receptors on platelets. Inhibition of MMP-2 by phenantroline and degradation of ADP by APT102, respectively, resulted in inhibition of TCIPA. Furthermore, both phenantroline and APT102 significantly down-regulated the surface abundance of platelet receptors. Caco-2 cells aggregate platelets, at least in part, via releasing MMP-2 and ADP. Modulation of MMP-2 and ADP actions could have therapeutic value in colonic cancer.
PUBLISHED
Keywords: Caco-2 Cells